Distinguishing Cardiac Amyloidosis and Hypertrophic Cardiomyopathy by Thickness and Myocardial Deformation of the Right Ventricle. (1st February 2022) - Liu, Hui; Bai, Peng; Xu, Hua-Yan; Li, Zhen-Lin; Xia, Chun-Chao; Zhou, Xiao-Yue; Gong, Liang-Geng; Guo, Ying-Kun
Abstract : Objectives . To compare right ventricular thickness (RVT) and deformation of cardiac amyloidosis (CA) and hypertrophic cardiomyopathy (HCM) patients. Methods . Sixty CA (mean age 58 ± 10 years; 33 males (55%)) and sixty HCM patients (mean age 55 ± 14 years; 27 males (45%)) were retrospectively enrolled. RVT, global radical peak strain (GRPS), global longitudinal peak strain (GLPS), and global circumferential peak stain (GCPS) were analyzed. To determine the cutoff values of the RVT and RV strain parameters for distinguishing CA from HCM, the areas under the receiver operating characteristic curve (AUCs) were analyzed. Results . RVT of CA patients was significantly thicker than that of HCM patients (7.8 ± 2.1 vs 5.9 ± 1.3, p  < 0.001). Moreover, significantly decreased RV-GRPS (12.1 ± 6.9 vs 23.5 ± 12.1, p  < 0.001), RV-GCPS (−3.4 ± 2.2 vs −5.6 ± 3.5, p  < 0.001), and RV-GLPS (−4.6 ± 2.3 vs −11.1 ± 4.9, p  < 0.001) were observed in CA patients compared with HCM patients. RVT and RV strain demonstrate comparable diagnostic accuracy in differentiating CA from HCM. In particular, RV-GLPS combined with RVT showed the best performance for discriminating CA from HCM (AUC = 0.92, 95% CI: 0.85 to 0.96, p  = 0.0001). Conclusions . Right ventricular myocardial thickness and deformation of CA patients was more severe than HCM patients. RV-GLPS combined with RVT presents an excellent diagnostic performance in distinguishing CA and HCM.